Dual energy CT with photon counting and dual source systems: comparative evaluation. (5th November 2015) - Atak, Haluk; Shikhaliev, Polad M
Abstract: Recently, new dual energy (DE) computed tomography (CT) systems—dual source CT (DSCT) and photon counting CT (PCCT) have been introduced. Although these systems have the same clinical targets, they have major differences as they use dual and single kVp acquisitions and different x-ray detection and energy resolution concepts. The purpose of this study was theoretical and experimental comparisons of DSCT and PCCT. The DSCT Siemens Somatom Flash was modeled for simulation study. The PCCT had the same configuration as DSCT except it used a photon counting detector. The soft tissue phantoms with 20, 30, and 38 cm diameters included iodine, CaCO3, adipose, and water samples. The dose (air kerma) was 14 mGy for all studies. The low and high energy CT data were simulated at 80 kVp and 140 kVp for DSCT, and in 20–58 keV and 59–120 keV energy ranges for PCCT, respectively. The experiments used Somatom Flash DSCT system and PCCT system based on photon counting CdZnTe detector with 2 × 256 pixel configuration and 1 × 1 mm 2 pixels size. In simulated general CT images, PCCT provided higher contrast-to-noise ratio (CNR) than DSCT with 0.4/0.8 mm Sn filters. The PCCT with K-edge filter provided higher CNR than the PCCT with a Cu filter, and DSCT with 0.4 mm Sn filter provided higher CNR than the DSCT with a 0.8 mm Sn filter. In simulated DE subtracted images, CNR of the DSCT was comparable to the PCCT with a Cu filter. However, DE PCCT with Ho a K-edge filter provided 30–40% higher CNR than the DE DSCT with 0.4/0.8 mm Sn filters. The experimental PCCT provided higher CNR in general imaging compared to the DSCT. In experimental DE subtracted images, the DSCT provided higher CNR than the PCCT with a Cu filter. However, experimental CNR with DE PCCT with K-edge filter was 15% higher than in DE DSCT, which is less than 30–40% increase predicted by the simulation study. It is concluded that ideal PCCT can provide substantial advantages over ideal DSCT in CT imaging including DE subtracted CT. However, the limitations of the PCCT detector does not allow it to reach its full potential and therefore further efforts are needed to improve PCCT detectors.